Role of Envelope Glycoprotein Complexes in Cell-Associated Spread of Human Cytomegalovirus - Nina Weiler; Caroline Paal; Kerstin Adams; Christopher Calcaterra; Dina Fischer; Richard James Stanton; Dagmar Stöhr; Kerstin Laib Sampaio; Christian Sinzger (Viruses, 2021)
The role of viral envelope glycoproteins, particularly the accessory proteins of trimeric and pentameric gH/gL-complexes, in cell-associated spread of human cytomegalovirus (HCMV) is unclear. We aimed to investigate their contribution in the context of HCMV variants that grow in a strictly cell-associated manner. In the genome of Merlin pAL1502, the glycoproteins gB, gH, gL, gM, and gN were deleted by introducing stop codons, and the mutants were analyzed for viral growth. Merlin and recent HCMV isolates were compared by quantitative immunoblotting for expression of accessory proteins of the trimeric and pentameric gH/gL-complexes, gO and pUL128. Isolates were treated with siRNAs against gO and pUL128 and analyzed regarding focal growth and release of infectious virus. All five tested glycoproteins were essential for growth of Merlin pAL1502. Compared with this model virus, higher gO levels were measured in recent isolates of HCMV, and its knockdown decreased viral growth. Knockdown of pUL128 abrogated the strict cell-association and led to release of infectivity, which allowed cell-free transfer to epithelial cells where the virus grew again strictly cell-associated. We conclude that both trimer and pentamer contribute to cell-associated spread of recent clinical HCMV isolates and downregulation of pentamer can release infectious virus into the supernatant.